If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(8 + 4h) = 0 (8 * -2 + 4h * -2) = 0 (-16 + -8h) = 0 Solving -16 + -8h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -8h = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -8h = 0 + 16 -8h = 0 + 16 Combine like terms: 0 + 16 = 16 -8h = 16 Divide each side by '-8'. h = -2 Simplifying h = -2
| x=5.6+1.4y | | 123+70=180 | | 2g+5=-3 | | (-7n/12)(9n/14) | | 9-5x=6x | | (2y-3)/(y+3)=5/7 | | 2h+5=3 | | 5x+3=10x+-7 | | 123+75=180 | | (-55)-(-88)= | | 6(7+x)+5x=0 | | -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 | | 176+4= | | 5x=7y+28 | | 9+5a=2a+5 | | 2x-1/3x=15 | | (3/8)(8/3)(n) | | (5/16)+(2/3)x=(1/4)-(1/6)x | | (-72)+36= | | (3/8)(8/3) | | A/4+7=22 | | 1-1/2-1/3 | | 2(0.6x+x)= | | (3k-3)(7k+7)= | | -8=p-5 | | -10b+2b+b=0 | | 5x+17x-8=180 | | 2(1.2)= | | (-76)+(-84)= | | (3x-6)(3x-6)=0 |